Agricultural or horticultural fungicide composition and method for controlling plant pathogen (2014)
A composition having a stable and high fungicidal effect against a cultivated crop infected by a plant pathogen is provided. An agricultural or horticultural fungicide composition containing, as active ingredients, (a) fluazinam or its salt and (b) a strobilurin compound or its salt is provided; in addition, a method for controlling a plant pathogen by applying the subject agricultural or horticultural fungicide composition to a plant or a soil is provided; and furthermore, a method for controlling a plant pathogen by applying (a) fluazinam or its salt and (b) a strobilurin compound or its salt to a plant or a soil is provided.